Workplace violence, psychological stress, sleep quality and subjective health in Chinese doctors: a large cross-sectional study. Issue 12 (7th December 2017) - Sun, Tao; Gao, Lei; Li, Fujun; Shi, Yu; Xie, Fengzhe; Wang, Jinghui; Wang, Shuo; Zhang, Shue; Liu, Wenhui; Duan, Xiaojian; Liu, Xinyan; Zhang, Zhong; et al.
Abstract : Background: Workplace violence (WPV) against healthcare workers is known as violence in healthcare settings and referring to the violent acts that are directed towards doctors, nurses or other healthcare staff at work or on duty. Moreover, WPV can cause a large number of adverse outcomes. However, there is not enough evidence to test the link between exposure to WPV against doctors, psychological stress, sleep quality and health status in China. Objectives: This study had three objectives: (1) to identify the incidence rate of WPV against doctors under a new classification, (2) to examine the association between exposure to WPV, psychological stress, sleep quality and subjective health of Chinese doctors and (3) to verify the partial mediating role of psychological stress. Design: A cross-sectional online survey study. Setting: The survey was conducted among 1740 doctors in tertiary hospitals, 733 in secondary hospital and 139 in primary hospital across 30 provinces of China. Participants: A total of 3016 participants were invited. Ultimately, 2617 doctors completed valid questionnaires. The effective response rate was 86.8%. Results: The results demonstrated that the prevalence rate of exposure to verbal abuse was the highest (76.2%), made difficulties (58.3%), smear reputation (40.8%), mobbing behaviour (40.2%), intimidation behaviour (27.6%), physical violence (24.1%) and sexual harassment (7.8%). Exposure to WPV significantly affected the psychological stress, sleep quality and self-reported health of doctors. Moreover, psychological stress partially mediated the relationship between work-related violence and health damage. Conclusion: In China, most doctors have encountered various WPV from patients and their relatives. The prevalence of three new types of WPV have been investigated in our study, which have been rarely mentioned in past research. A safer work environment for Chinese healthcare workers needs to be provided to minimise health threats, which is a top priority for both government and society.